Comparison of ankle dorsiflexion in closed kinematic chain of football players and ice hockey players - Liska, D.; Švantner, R.; Batalik, L. (Kinesiologia Slovenica, 2021)
Limitation in ankle dorsiflexion is associated with the development of injury to the musculoskeletal system. However, little is known about the impact of different sports disciplines on the dorsiflexion range of motion in the ankle joint. Therefore, the aim of the study is to compare the dorsiflexion range of motion of ice hockey players and football players. The sample included 26 professional football players with an average age of 22.46 (± 3.75). The control group included 37 professional ice hockey players with an average age of 24.62 (± 4.34). The range of motion of ankle dorsiflexion in closed kinematic chain was tested using a mobile phone application. The mean ankle dorsiflexion range of motion in football players was 41.40° (± 5.36) at the right ankle joint and 45° (± 5.91) at the left ankle joint. The mean ankle dorsiflexion range of motion in football players was 42.49° (± 6.92) in the right ankle joint and 45.92° (± 5.45) in the left ankle joint. The ranges of motion of the dorsiflexion of the right ankle (p <0.016) and the dorsiflexion of the left ankle (p - 0.031) ranges of motion in ice hockey players were significantly higher compared to football players. The average ankle dorsiflexion range of motion in the closed kinematic chain of ice hockey players was significantly higher compared to football players.